Aerobic training reduces blood pressure and waist circumference and increases HDL-c in metabolic syndrome: a systematic review and meta-analysis of randomized controlled trials - Lemes, Italo Ribeiro [UNESP]; Turi-Lynch, Bruna Camilo [UNESP]; Cavero-Redondo, Ivan; Linares, Stephanie Nogueira; Monteiro, Henrique Luiz [UNESP] (Elsevier B.V., 2018)
The objective of this study is to estimate the effect of aerobic training (AT) on metabolic syndrome (MetS) outcomes. The Medline, EMBASE, SPORTDiscus, The Cochrane Library, and PEDro databases were searched from inception to May 2017. Two independent reviewers selected the studies and assessed their quality and data. The pooled mean differences between intervention groups and the control group were calculated using a random-effect model. Only randomized controlled trials that compared the effect of AT on MetS with a control group were included. Seventeen published studies were included in the meta-analysis. Systolic and diastolic blood pressure were significantly reduced (-5.11 mmHg [95% confidence interval [CI] -7.36, -2.85] and -2.97 mmHg [-4.99, -0.94], respectively), following AT. There was also a significant reduction in waist circumference (-2.18 cm [-95% CI -3.75, 0.62]) and a significant increase in high-density lipoprotein cholesterol (95% CI 3.15 mg/dL [-5.30, -1.01]). The pooled effect showed a reduction of 7.64 mg/dL [95% CI -17.65, 2.37] in triglycerides and 1.36 mg/dL [95% CI -4.11, -1.40] in fasting glucose. This systematic review and meta-analysis provides an overview of the evidence supporting AT as an effective approach to reduce blood pressure levels and waist circumference and increase high-density lipoprotein cholesterol levels. These changes may help to reduce the risk of stroke mortality and mortality from heart disease in people with MetS. (C) 2018 American Heart Association. All rights reserved.
Keywords: Aerobic fitness; diabetes; exercise training; heart disease